Apply the distributive property.

Apply the distributive property.

Apply the distributive property.

Combine the opposite terms in <math><mstyle displaystyle="true"><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>y</mi><mrow><mo>(</mo><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>y</mi><mo>)</mo></mrow><mo>+</mo><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>y</mi><mrow><mo>(</mo><mn>2</mn><mi>x</mi><mi>y</mi><mo>)</mo></mrow><mo>-</mo><mn>2</mn><mi>x</mi><mi>y</mi><mrow><mo>(</mo><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>y</mi><mo>)</mo></mrow><mo>-</mo><mn>2</mn><mi>x</mi><mi>y</mi><mrow><mo>(</mo><mn>2</mn><mi>x</mi><mi>y</mi><mo>)</mo></mrow></mstyle></math> .

Reorder the factors in the terms <math><mstyle displaystyle="true"><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>y</mi><mrow><mo>(</mo><mn>2</mn><mi>x</mi><mi>y</mi><mo>)</mo></mrow></mstyle></math> and <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>x</mi><mi>y</mi><mrow><mo>(</mo><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>y</mi><mo>)</mo></mrow></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>2</mn><mo>⋅</mo><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>x</mi><mi>y</mi><mo>⋅</mo><mi>y</mi></mstyle></math> from <math><mstyle displaystyle="true"><mn>2</mn><mo>⋅</mo><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>x</mi><mi>y</mi><mo>⋅</mo><mi>y</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>y</mi><mrow><mo>(</mo><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup><mi>y</mi><mo>)</mo></mrow></mstyle></math> and <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Simplify each term.

Multiply <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> by <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> by adding the exponents.

Move <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> .

Use the power rule <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi></mrow></msup><msup><mrow><mi>a</mi></mrow><mrow><mi>n</mi></mrow></msup><mo>=</mo><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi><mo>+</mo><mi>n</mi></mrow></msup></mstyle></math> to combine exponents.

Add <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by adding the exponents.

Move <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by adding the exponents.

Move <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by adding the exponents.

Move <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Do you know how to Simplify (3x^2y-2xy)(3x^2y+2xy)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.